O-008 Comparison between tici 2b and tici 3. (23rd July 2017) - Goyal, N; Tsivgoulis, G; Frei, D; Turk, A; Baxter, B; Froehler, M; Mocco, J; Ishfaq, M; Hoit, D; Chang, J; Elijovich, L; Loy, D; et al.
Abstract : Background: Mechanical thrombectomy (MT) for acute ischemic stroke (AIS) patients with emergent large-vessel occlusions (ELVO) has become the standard of care. A recent meta-analysis of the 5 randomized trials demonstrated that 46% of patients in the intervention arm achieved mRS of 0–2 at 3 months. Considering the fact that significant numbers of patients still have residual disability at three months despite MT, it is important to consider other modifiable variables that might improve functional outcomes in patients with ELVO. Successful reperfusion post MT is the strongest modified predictor of the outcome. Thrombolysis in cerebral infarction (TICI) grades are current standard of care for assessment of degree of reperfusion post MT. Recently conducted trials defined both TICI 2b and 3 grades as successful reperfusion. In this multicenter study we sought to evaluate if there are any differences in safety and effectiveness outcomes between ELVO patients who achieved TICI 2b and those who achieved TICI 3 reperfusion post MT. Methods: We conducted an observational study on consecutive AIS patients with ELVO who underwent MT at 6 high-volume endovascular centers. Standard safety (3 month mortality, symptomatic intracranial hemorrhage) and effectiveness (3 month functional independence: modified Rankin Scale scores of 0–2) outcomes were compared between patients who had TICI 2b and TICI 3 reperfusion post MT. Results: The sample consisted of 583 patients with ELVO who underwent MT. A total of 416 patients achieved successful reperfusion (TICI 2b or 3) post MT. TICI 2b reperfusion was achieved in 216 (52%) patients [mean age 64±15, Male 50%, median NIHSS: 16 (IQR 12–20)], while 200 patients (48%) achieved TICI 3 reperfusion post MT [mean age 66±14, Male, 48%, median NIHSS 16 (IQR: 13–20)]. TICI 2b and TICI 3 reperfusion groups did not differ in terms of intravenous thrombolysis pretreatment (51% vs 56%, p=0.425), median onset to groin puncture time [minutes, median (IQR); 223 (157–318) vs 240 (176–311), p=0.850], median groin puncture to recanalization time [minutes, median (IQR); 38 (23–62 vs 41 (26–57), p=0.282) and 3 months mortality (22% vs 19%, p=0.523). TICI 3 reperfusion group had lower median discharge NIHSS [median (IQR) 3 (1–7) vs 5 (2-12), p=0.029), lower rates of symptomatic intracranial hemorrhage (6% vs 12%, p=0.035) and higher rates of functional independence at 3 months (55% vs 44%, p=0.050) compared to TICI 2b reperfusion group. In multivariate model after adjustment for potential confounders, TICI 3 reperfusion group was associated with greater neurological improvement during hospitalization (OR 1.009; 95% CI: 1.002–1.016, p=0.024), lower rates of sICH (OR 0.28; 95% CI: 0.10–0.78, p=0.027) and tended to have higher rates of 3 months functional independence (OR 1.80; 95% CI; 1.01–3.21, p=0.054) compared to TICI 2b group. Conclusions: TICI 3 reperfusion appears to be associated with better early outcomes in comparison to TICI 2b reperfusion in ELVO Patients treated with MT. Future clinical trials involving ELVO patients should differentiate between these reperfusion groups in terms of safety and effectiveness outcomes. Disclosures: N. Goyal: None. G. Tsivgoulis: None. D. Frei: None. A. Turk: None. B. Baxter: None. M. Froehler: None. J. Mocco: None. M. Ishfaq: None. D. Hoit: None. J. Chang: None. L. Elijovich: None. D. Loy: None. R. Turner: None. J. Mascitelli: None. K. Espaillat: None. A. Alexandrov: None. A. Arthur: None.